PENGGUNAAN METODE AMTSILATI DALAM MENINGKATKAN KUALITAS BACA KITAB KUNING PADA SANTRI DI MADRASAH DINIYAH PONDOK PESANTREN MAMBAUL ULUM, JABUNG-MALANG - Sunanul Annisyah; Muhammad Afifulloh; Atika Zuhrotus Sufiyana (VICRATINA, 2021)
This study consists of problems found during the study: learning to read the Yellow Book in Madrasah Diniyah Mambaul Ulum Jabung Malang. In addition, this study uses descriptive qualitative research methods that use observation techniques, interviews and documentation. Researchers found many findings, among others: 1) The condition of gold reading training in Madrasah Diniyah Mambaul Ulum was implemented since elementary education. 2) Santri should know the text of the Yellow Book and the location of lafadz, which will improve students' learning outcomes compared to KKM standards and allow them to reading and understand the Yellow Book correctly 3) Some obstacles due to lack of human resources There is one resource (human resources) in question that is boring and unassigned teachers.